Answer:
The correct option is;
The expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 - 6) = negative 18 and Negative 12 (1) minus 6 = negative 18
Explanation:
The parameters given are;
First expression 3 × X × (5 - 4) + 3 ×(X - 6)
Second expression -12 × X - 6
Therefore;
For the first expression, for all X, e have;
3 × X × 1 + 3 ×(X - 6) = -3·X + 3·X -18 = -18
The second expression gives -12·X - 6
When both expressions are equal, we have;
-12·X - 6 = -18
∴ X = (-18 + 6)/(-12) = 1
Hence the correct option is that the expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 - 6) = negative 18 and Negative 12 (1) minus 6 = negative 18.